The effects of lawsonia inermis pigmentation for superhydrophobic properties on cotton fabrics - Marsi, Noraini; Sidni, Wardah; Mohd Rus, Anika Zafiah; Abdul Rashid, Azrin Hani (Penerbit UTHM, 2020)
Nowadays, there are many things that can be produced easily by the help of modern technologies. This include the synthetic materials that can be developed by using any advance machine that was manufactured [1]. However, those synthetics materials that was developed may bring harm to the environment. Their particles can be spread resulting an unhealthy atmosphere. Thus, the natural resources was used to produce an authentic materials (Calarge, 2018). In the recent years, textile industry has been developed significantly and contributes to the growth of Malaysia’s economy [2]. It can be categorized as one of the complicated industries among the manufacturing industries such as food, cosmetics and pharmaceutical industries [3]. Thus, the textile industries require high water consumption and resulting on high discharge rate of wastewater that loaded with contaminants [2]. The generation of wastewater from textile industry comes from the manufacturing process of textile fabrics such as washing scouring bleaching, mercerizing, and dyeing and finishing process. The highest amount of wastewater that produced from textile industries come from the process of dyeing and finishing. The contaminants of water that produced by dyeing and finishing process include high suspended solids (SS), chemical oxygen demand (COD), biochemical oxygen demand (BOD), heat, colour, acidity, basicity, and other organic pollutants [4]. This matter has to be seriously concerned as it may lead to allergic responses, eczema, and also affect the liver, lungs, and immune system of humans as well as animals [3]. The purpose for the project of the effects of Lawsonia Inermis was basically to produce a natural pigment that may not harm the environment